2011
DOI: 10.1097/ta.0b013e318220ad7e
|View full text |Cite
|
Sign up to set email alerts
|

Platelet Transfusion: An Unnecessary Risk for Mild Traumatic Brain Injury Patients on Antiplatelet Therapy

Abstract: Platelet transfusion did not improve short-term outcomes after MTBI. Further randomized controlled trials need to be done to truly assess if there is no benefit in platelet transfusion in patients taking antiplatelet agents suffering an MTBI. Because the overall outcome in MTBI patients is favorable, platelet transfusion in these patients may not be indicated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
49
0
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(53 citation statements)
references
References 23 publications
3
49
0
1
Order By: Relevance
“…Similar data were reported by Downey in a retrospective study involving two level 1 Trauma Centres over a 4 years period [36]. Ivascu [37] and Fortuna [38] in two separate studies observed a non significant trend towards higher mortality in patients with traumatic brain injury treated with platelets transfusion, but patients transfused were older and presented a lower GCS and higher ISS [35]. All of these studies though, have some weakness: they are retrospective, relative small and the indication and timing for platelet transfusion were not standardized.…”
Section: Resultssupporting
confidence: 81%
See 1 more Smart Citation
“…Similar data were reported by Downey in a retrospective study involving two level 1 Trauma Centres over a 4 years period [36]. Ivascu [37] and Fortuna [38] in two separate studies observed a non significant trend towards higher mortality in patients with traumatic brain injury treated with platelets transfusion, but patients transfused were older and presented a lower GCS and higher ISS [35]. All of these studies though, have some weakness: they are retrospective, relative small and the indication and timing for platelet transfusion were not standardized.…”
Section: Resultssupporting
confidence: 81%
“…A recent metaanalysis of six studies failed to demonstrate any clear benefit of platelet transfusions in patients with either spontaneous or traumatic intracranial haemorrhage [34]. In a retrospective analysis of a cohort of 113 patients with traumatic intracerebral haemorrhage (TICH) on antiplatelet medications, Washington [35] et al, couldn't find any statistically significant difference in outcome between patients treated with platelets and those who were not transfused. Similar data were reported by Downey in a retrospective study involving two level 1 Trauma Centres over a 4 years period [36].…”
Section: Resultsmentioning
confidence: 99%
“…Traumatic and other intracranial hemorrhages not requiring an operation are also a relative indication for reversal, with some authors advocating for reversal in all cases [ 5 , 17 , 24 , 25 ]. This too remains a point of debate among clinicians though, as some trauma literature opposes platelet transfusion [ 26 ]. The only approved mode of reversal when necessary is to transfuse platelets, as most of these agents are irreversible [ 27 ].…”
Section: Emergency Reversal Of Antiplatelet and Anticoagulant Agents mentioning
confidence: 99%
“…In cases of antiplatelet therapy, studies have shown worse outcomes in patients with traumatic brain injury [16,17]. However, the results for platelet transfusion in patients on antiplatelet therapy have been inconclusive, with some studies showing no benefit in clinical outcome [18,19], others showing an improved outcome [16], and still others showing a worsened outcome [20]. Thus, while platelet transfusion is typically considered a standard of care [21], the question of the risk to benefit ratio of platelet transfusions in these circumstances remains, particularly in situations of mild traumatic brain injury.…”
Section: Antiplatelet Therapy/platelet Dysfunctionmentioning
confidence: 99%